2022
DOI: 10.32604/or.2022.026459
|View full text |Cite
|
Sign up to set email alerts
|

Is autophagy induction by PARP inhibitors a target for therapeutic benefit?

Abstract: PARP inhibitors have proven to be effective in conjunction with conventional therapeutics in the treatment of various solid as well as hematologic malignancies, particularly when the tumors are deficient in DNA repair pathways.However, as the case with other chemotherapeutic agents, their effectiveness is often compromised by the development of resistance. PARP inhibitors have consistently been reported to promote autophagy, a process that maintains cellular homeostasis and acts as an energy source by the degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…Autophagy induction has been shown to be associated with various therapeutic modalities, with different functions, including cytotoxic, cytoprotective, cytostatic and non-protective forms. Importantly, and as mentioned in previous publications [3][4][5][6][7] and largely accepted in the literature, the nature of the induced autophagy is dependent on the cell line as well as the nature of the chemical compound being utilized. As summarized in Table 1, the majority of the studies showed that BET inhibitors induced autophagy in different tumor models with two main roles, cytotoxic and cytoprotective.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Autophagy induction has been shown to be associated with various therapeutic modalities, with different functions, including cytotoxic, cytoprotective, cytostatic and non-protective forms. Importantly, and as mentioned in previous publications [3][4][5][6][7] and largely accepted in the literature, the nature of the induced autophagy is dependent on the cell line as well as the nature of the chemical compound being utilized. As summarized in Table 1, the majority of the studies showed that BET inhibitors induced autophagy in different tumor models with two main roles, cytotoxic and cytoprotective.…”
Section: Discussionmentioning
confidence: 84%
“…This manuscript is one of a series of papers that highlight the different roles of autophagy in response to various cancer therapeutic modalities. Our previous publications assessed the influence of autophagy in tumor cells on the response/sensitivity to radiation [ 1 ], cisplatin [ 2 ], microtubule poisons [ 3 ], hormonal therapies in estrogen-positive breast cancer [ 4 ], PARP inhibitors [ 5 ], Topoisomerase I poisons [ 6 ] and, most recently, temozolomide [ 7 ]. Our overarching goal is to determine whether there are particular therapeutic modalities where the preclinical data, and, where available, clinical trials, support the inclusion of autophagy inhibition as an adjuvant approach.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is an important mode of energy catabolism in the organism ( Gatica et al, 2015 ), whose main function is to recycle damaged or unwanted cellular components, thereby maintaining cell viability, and is often considered a protective mechanism ( Koleini and Kardami, 2017 ). Autophagy is involved in maintaining intracellular homeostasis in most types of cardiovascular cells, especially cardiomyocytes ( Taneike et al, 2010 ; Gottlieb and Mentzer, 2013 ; Xiao et al, 2019 ; Luan et al, 2021 ; Elshazly et al, 2022 ). Several studies have shown that under normal conditions, decreased levels of autophagy are an adaptive response of the body to the heart to prevent cardiomyocyte death ( Mei et al, 2015 ).…”
Section: Molecular Mechanisms Of Chemotherapy-related Cardiotoxicitymentioning
confidence: 99%
“…ChatGPT mentioned that autophagy may have different roles, however omitting the non-protective and cytostatic roles (Elshazly and Gewirtz, 2023c;Elshazly and Gewirtz, 2023d;Sharma et al, 2014b). ChatGPT highlighted that the specific autophagic response is based on the tumor/cell line, and the chemical nature of the compounds being utilized, which is widely accepted in the scientific literature Elshazly and Gewirtz, 2023d; Elshazly et al, 2022). In non-protective autophagy, autophagy induction or targeting does not significantly contribute to tumor cell survival Xu et al, 2022); for instance, non-protective autophagy is induced by a combination of fulvestrant plus palbociclib in ER + breast cancer cell lines, where autophagy targeting genetically or pharmacologically does not affect the cells viability (Finnegan et al, 2022a;Finnegan et al, 2022b).…”
Section: Q5; What Is the Connection Between Senescence And Autophagy ...mentioning
confidence: 99%